Produtividade do milho safrinha em sistema plantio direto em função da utilização de espécies de cobertura e aplicação de calcário em superfície - Siqueira Filho, Roberto (2005)
The present work had for objective to evaluate the effect of different covering crops and the surface liming in no-tillage system, determining the content of dry biomass produced by each one of these species and the effect of the liming on the chemical properties of the soil and its consequent effect in the yield components and the productivity of the winter maize crop. The experiment was lead in period 2003/2004, in the experimental farm of the IAPAR (Paraná State Agronomic Institute), in one soil classified as Eutroferric Red Latosol, in the city of Palotina - PR. The treatments had been constituted of five vegetal covering species (millet, guandu, foxtail millet, association of guandu with millet and pousio), in combinations with and without surface liming. 3,2 t ha-1 of dolomitic limestone had been applied in surface in certain plots, without incorporation. It was determined that the desiccation of green fertilizers would be carried through when the species emitted string beans or panicle. At the moment of the desiccation of the plots the collections of biomass for determination of the production and the speed of decomposition of each one of the species had been initiated, happening again themselves this sampling 15, 30 and 45 days after. Also stratified soil samples had been collected (0 0,10 and 0,10 0,20 m) in each plot, in the line of sowing of the species, for determination of pH, levels of P, M.O., H + Al, K, Ca and Mg and values of SB, CTC, V% and m%. The sowed maize were the simple modified hybrid AG-9010. The experiment in the field was conducted until being carried through the harvest of the plots and determined the productivity. Also the determination of the components of the production (number of grains for spike, mass of the grains for spike and mass of 100 grains) in function of the vegetal species and application or not of limestone in each plot was carried through. One concluded that, independently of the species of covering, the surface liming is efficient in the correction of the acidity of the soil and increase of pH and levels of calcium and magnesium in the 0 0,10 m layer. At guandu plots occurred increase of the level of phosphorus of the soil in the depth of 0,10 0,20 m, however this fact must be associated to the liming, a time that this species presents great capacity to acidify of the soil. The Millet presented greater production of dry matter and bigger tax of decomposition, followed for the association of millet with guandu and guandu. Grass mills also presented minor residue production and lesser tax of decomposition during the period of 45 days. The combination of liming more guandu as species of soil covering before the winter maize crop, results in profits in the mass of the spike and mass of 100 grains, with positive consequences in the productivity